2015
DOI: 10.1021/ja5121088
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Conversion of CO2to CO Using Tin and Other Inexpensive and Easily Prepared Post-Transition Metal Catalysts

Abstract: The development of affordable electrocatalysts that can drive the reduction of CO2 to CO with high selectivity, efficiency, and large current densities is a critical step on the path to production of liquid carbon-based fuels. In this work, we show that inexpensive triflate salts of Sn(2+), Pb(2+), Bi(3+), and Sb(3+) can be used as precursors for the electrodeposition of CO2 reduction cathode materials from MeCN solutions, providing a general and facile electrodeposition strategy, which streamlines catalyst sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
192
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(211 citation statements)
references
References 43 publications
12
192
0
1
Order By: Relevance
“…12,15,45 The observed improvement in CO 2 conversion efficiency for the OD-Cu electrode in this study can be due to the careful acid pretreatment of the electrode, probably removing existing active species for H 2 , and the subsequent 400 °C annealing step, in contrast to the 500 °C heat treatment previously used to build the copper oxide layers. 12,21,45,46 Next, the electrocatalytic performance of Cu-Sn exhibited a remarkably high FE towards CO, achieving > ~90% at −0.6 V ( Figure 1b). A long-term stability of the Cu-Sn was observed for 14 h, which showed an initial ~95% CO FE for 6 h; subsequently decreasing to ~90%, with the H 2 FE increasing over time from ~8% to ~12%.…”
Section: Electrochemical Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…12,15,45 The observed improvement in CO 2 conversion efficiency for the OD-Cu electrode in this study can be due to the careful acid pretreatment of the electrode, probably removing existing active species for H 2 , and the subsequent 400 °C annealing step, in contrast to the 500 °C heat treatment previously used to build the copper oxide layers. 12,21,45,46 Next, the electrocatalytic performance of Cu-Sn exhibited a remarkably high FE towards CO, achieving > ~90% at −0.6 V ( Figure 1b). A long-term stability of the Cu-Sn was observed for 14 h, which showed an initial ~95% CO FE for 6 h; subsequently decreasing to ~90%, with the H 2 FE increasing over time from ~8% to ~12%.…”
Section: Electrochemical Measurementsmentioning
confidence: 97%
“…18 Rosenthal and co-workers have reported a generalized strategy for the electrodeposition of inexpensive electrocatalytic films from triflate salts of Bi 3+ , Sb 3+ , Sn 2+ , and Pb 2+ in organic media. [19][20][21] When the Bi-based electrodes are used for electrochemical CO 2 reduction in acetonitrile with a low overpotential of 250 mV, the 4 electrocatalysts are highly selective towards CO only when an appropriate ionic liquid is present in the system (1-ethyl-3-methylimidazolium hexafluorophosphate [EMIM]PF 6 , or 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM]PF 6 , with an average 81% CO FE with [25][26][27][28][29][30] mA cm −2 ). [19][20][21] These seminal studies have thus clearly indicated that non-noble catalysts have the capability to compete with noble metals for CO 2 reduction.…”
mentioning
confidence: 99%
“…Except for Sn, partially oxidized Bi/Bi 3+ materials have shown excellent CO-selective capabilities in ionic liquid [121][122][123][124]. Recently, the Rosenthal group synthesized a rosebud-type Bi thin film on a glassy carbon electrode (GCE) by electrochemical deposition (Fig.…”
Section: Partially Oxidized Metal Catalystsmentioning
confidence: 99%
“…Elegant advances in traditional approaches to CO 2 reduction driven by electrical and/or solar inputs using homogeneous (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), heterogeneous (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and biological (7,(27)(28)(29)(30)(31) catalysts point out key challenges in this area, namely (i) the chemoselective conversion of CO 2 to a single product while minimizing the competitive reduction of protons to hydrogen, (ii) long-term stability under environmentally friendly aqueous conditions, and (iii) unassisted light-driven CO 2 reduction that does not require external electrical bias and/or sacrificial chemical quenchers. Indeed, synthetic homogeneous and heterogeneous CO 2 catalysts are often limited by product selectivity and/or aqueous compatibility, whereas enzymes show exquisite specificity but are generally less robust outside of their protective cellular environment.…”
mentioning
confidence: 99%